The first stages of formation and historical development of the Uzbek pottery lexicon - Kadirova Mashhura (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
the article examines the emergence, historical stages and development of pottery lexicon, which is considered the leading branch of applied art. the research done on it was analyzed. Also, the lexicon of people engaged in pottery and the things used in the process was considered.